Seletividade penal e o princípio da proporcionalidade - Ramos, Luciano Lopes Nogueira (2025)
This research addresses the principle of the prohibition of insufficient protection, whose debate began in Germany following two landmark abortion rulings. In these cases, it was held that the right to life of the unborn was inadequately protected (Untermassverbot). The introduction provides an overview of how the German Federal Constitutional Court initially addressed the principle of the prohibition of insufficient protection, as well as references to the principle in rulings by the Brazilian Federal Supreme Court. The first chapter discusses the legally protected interest (Rechtsgut). The second chapter examines imprisonment, theories of punishment, criminal law schools, and the historical development of custodial sentences. The third chapter analyzes the principle of proportionality in both Germany and Brazil. The fourth chapter directly explores the principle of the prohibition of insufficient protection, while also drawing from lessons learned from the principle of proportionality. It highlights the disproportionate sentencing between the minimum penalty for homicide, which is six years under Article 121, caput, of the Brazilian Penal Code, and the minimum penalty for armed robbery involving violence, serious threats, or the use of firearms or explosives, which is six years and eight months under Article 157, § 2-A, I and II, of the Brazilian Penal Code. The conclusion acknowledges the recognition of the principle of the prohibition of insufficient protection in Brazil, reiterates the sentencing disparity mentioned, and proposes a constitutional mutation as a solution. This would entail interpreting a violation of the principle as a constitutional omission in the duty to protect fundamental rights. The proposal also includes the application of constitutional remedies, the requirement that such control be exercised solely by the Federal Supreme Court, the notification of the Legislative Branch to correct the imbalance, and the possibility of the Court issuing binding guidelines in case of persistent violations